Impact of a large-scale fruit and vegetable irrigation scheme on the micro-epidemiology of malaria in southwest Ethiopia - Tewodros Getachew; Ahmed Zeynudin; Teshome Degefa; Ming-Chieh Lee; Delenasaw Yewhalaw (BMC, 2024)
Abstract Background Malaria continues to represent an important public health problem in Ethiopia. The expansion of irrigated agricultural development projects turns out to be a major impediment to long-lasting and sustainable malaria prevention and control efforts in the country. The aim of this study was to determine the micro-epidemiology of malaria and associated risk factors in and around Gojeb Horizon Irrigation Plantation in southwest Ethiopia. Methods A community-based comparative cross-sectional study was conducted from May to June 2018 in Gimbo District, southwest Ethiopia. A total of 186 households (94 from irrigated village and 92 from non-irrigated village) were randomly selected from among the communities living around the Gojeb Horizon plantation. In total, 718 individuals (368 from irrigated village and 350 from non-irrigated village) were recruited from the selected households. A finger-prick blood sample was obtained from each participant. Socio-demographic data from the households and individual study participants were collected using a semi-structured questionnaire. Multivariate regression was used to assess factors associated with micro-epidemiology of malaria. P-value < 0.05 was considered statistically significant. Results The prevalence of malaria in irrigated and non-irrigated villages was 8.2% and 3.4%, respectively. Plasmodium falciparum, Plasmodium vivax and mixed infections accounted for 57.1%, 38.1%, and 4.8% of the cases, respectively. Individuals living in the irrigated villages were 2.53 (95% CI: 1.23-5.20) times at higher risk of Plasmodium infection as compared to those living in the non-irrigated village. Age (AOR = 1.03, 95% CI: 1.01-1.06) and non-use of long-lasting insecticidal net (AOR = 2.72, 95% CI: 1.03-7.22) were co-predictors of malaria infection in the area. Conclusion This study revealed that communities living in irrigation village were at a higher risk of Plasmodium infection than those living in non-irrigated village, which necessitates the development of tailored interventions that are both targeted and customized.